Editorial of the special issue of the 10th workshop on biomedical and bioinformatics challenges for computer science—BBC 2017 - Agapito, Giuseppe (2019)
Agapito, G., Cannataro, M., Castelli, M., Dondi, R., & Zoppis, I. (2018). Editorial of the Special Issue of the 10th Workshop on Biomedical and Bioinformatics Challenges for Computer Science—BBC 2017. Computers, 7(1), 2. DOI: 10.3390/computers7010017